Batch process of mercury (II) removal using CNTs grown on GACs - Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; Ismail, Nur Hafizah (2011)
This research project was performed to study the performance of carbon nanotubes (CNT) grown on granular activated carbon (GAC) as an adsorbent for removal of heavy metal (mercury) from aqueous solution. The effect of pH, agitation speed, contact time and CNT dosage was studied for optimal adsorption of mercury in the aqueous solution. Design Expert software was used to determine the number of runs and its variations, which are 18 runs. It was found that the optimal condition for mercury (II) ions adsorption occurred at adsorbent dosage of 5 mg, pH value of 5, contact time of 120 minutes and agitation speed of 150 rpm with a value of 0.031 mg/L residual amount.